Prognostic factors for ovarian metastases from primary gastric cancer. Issue 4 (1st July 2008) - Wang, J.; Shi, Y.-K.; Wu, L.-Y.; Wang, J.-W.; Yang, S.; Yang, J.-L.; Zhang, H.-Z.; Liu, S.-M.
Abstract : The purpose of this study was to analyze prognostic factors for ovarian metastases from primary gastric cancer, helping establish optimal strategy in ameliorating survival for this entity. Clinical data of 68 consecutive patients histologically diagnosed with ovarian metastases from primary gastric cancer were accrued from 1096 cases with female gastric cancer. Metachronous surgery was performed on 36 patients and 32 received synchronous surgery. There were 14 patients treated with surgery alone and 54 with combined modality therapy. After the median follow-up time of 9.1 months, the median survival time (MST) of 12.4 months was observed for all patients. Patients treated with synchronous surgery tended to have an inferior survival compared with those treated with metachronous surgery (MST: 10.9 vs 14.3 months; P = 0.100). Combined modality showed a significantly better MST compared with surgery alone (13.6 vs 7.9 months; P = 0.004). Chemotherapy cycles (more than four or less than or equal to four) were found to have an impact on survival (MST: 14.3 vs 9.4 months; P = 0.031). Peritoneal metastases, lymphovascular involvement, and unilateral ovarian metastasectomy were independent unfavorable prognostic factors. Combined modality therapy as primary therapy resulted in good outcome, and more aggressive chemotherapy (more than four cycles) was accompanied by an improvement in survival. Innovative systemic treatments need to be explored in treatment of peritoneal metastases and lymphovascular involvement. Bilateral oophorectomy was considered when ovarian metastases were histologically diagnosed.